2010
DOI: 10.1891/1541-6577.24.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Condom Use Among Mexican Adolescents

Abstract: Mexican adolescents continue to be at increased risk for HIV infection due to inconsistent condom use. The purpose of this study was to identify predictors of condom use intentions and condom use among Mexican adolescents who participated in a randomized control trial designed to test a sexual-risk reduction intervention. Data from sexually active adolescents 17 to 21 years (n = 157) of age who were assigned to the control group were analyzed 48 months post intervention. Regression analysis showed that positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
1
17
1
2
Order By: Relevance
“…Among all subjective norms, parental norms were the most influential toward young people’s intentions to abstain, highlighting the level of influence that parents can have in enhancing effective promotion of sexual abstinence among Swazi in-school youths. The positive impact that parents can have on adolescent sexual behavior has been emphasized by numerous studies [19], [20], [45] and is also consistent with national survey data in Swaziland, which indicate that parenting and family support are key factors in limiting the spread of HIV [46]. Contextual explanations for these findings could be related to the Swazi traditional norm in girls of retaining premarital virginity, which promotes sexual abstinence.…”
Section: Discussionsupporting
confidence: 73%
“…Among all subjective norms, parental norms were the most influential toward young people’s intentions to abstain, highlighting the level of influence that parents can have in enhancing effective promotion of sexual abstinence among Swazi in-school youths. The positive impact that parents can have on adolescent sexual behavior has been emphasized by numerous studies [19], [20], [45] and is also consistent with national survey data in Swaziland, which indicate that parenting and family support are key factors in limiting the spread of HIV [46]. Contextual explanations for these findings could be related to the Swazi traditional norm in girls of retaining premarital virginity, which promotes sexual abstinence.…”
Section: Discussionsupporting
confidence: 73%
“…The ¡Cuídate! program was tested with an urban Puerto Rican adolescent population in the mainland US and demonstrated effectiveness, including reduced sexual activity and number of sexual partners and increased condom use (Alvarez, Villarruel, Zhou, & Gallegos, ; Villarruel, Jemmott, & Jemmott, ; Villarruel, Jemmott, Jemmott, & Ronis, ). However, the program had not been tested with youth from Mexico and Central America living in the rural South.…”
Section: A Culturally‐tailored Interventionmentioning
confidence: 99%
“…Accordingly, both greater confidence [9] and perceived self-efficacy [14, 15] have been associated with greater condom use. Emerging literature has demonstrated that confidence in one's ability to use a condom is as important as attitudes toward condoms for promoting future condom use [10]. Hence, understanding user confidence and its determinants may aid the development of strategies to promote consistent and effective condom use.…”
Section: Introductionmentioning
confidence: 99%